Factors Influencing Mobile Banking Usage and Its Impact on Consumptive Behavior - Zuliarni, Sri; Mustika, Bunga Amelia (Politeknik Negeri Bengkalis, 2024)
This study aims to examine the effect of mobile banking usage on the consumptive behavior via interveningvariable the use of mobile banking. This research method is quantitative with data collection techniques using surveytechniques using questionnaires. The sampling technique uses a purposive sampling technique. The research sample was145 mobile banking apps users from five universities students in Batam City. The results also show that the completenessof the feature, service quality, trust, social influence has a positive effect on consumptive behavior.